Applicability of the hour of life approach in hyperbilirubinemia among Filipino term infants - Villanueva-Uy, Maria Esterlita T.; G. Uy, Herbert; Amarillo, Maria Lourdes E. (Frontiers in Pediatrics, 2022)
Background Hyperbilirubinemia remains a common morbidity among infants. Additional research on bilirubin kinetics and associated risk factors will contribute to providing a more targeted management approach for the Filipino infant. Objective To develop a Filipino bilirubin nomogram by studying bilirubin patterns during the first 5 days of life. Methodology This prospective study recruited 1,412 stable, full-term infants (≥37 weeks age of gestation) born at the Philippine General Hospital (PGH). Using the Dräger-Minolta JM-103 jaundice meter, transcutaneous bilirubin (TcB) levels were determined at the 3rd, 6th, 12th, 24th, 36th, 48th, 72nd, 96th, and 120th hour of life (HOL). A bilirubin nomogram was created using the averages of 3 TcB forehead and sternal measurements at each time epoch. Simultaneous measurement of TcB and total serum bilirubin (TsB) on a subset of 106 infants was done to determine correlation. Results Correlation coefficients were high between TsB and forehead TcB (r2 = 0.88), and between TsB and sternal TcB (r2 = 0.91). The Filipino bilirubin nomogram reflected a steep rise until the 48th hour, followed by plateauing of values. Inadequate nursing and bilirubin levels at 12th and 48th HOL were risk factors for developing significant hyperbilirubinemia at 72nd HOL. Conclusion TcB is a reliable, non-invasive bilirubin screening tool. Among healthy, full-term, Filipino infants, their nomogram features a sudden increase in bilirubin values during the first 48 h, followed by a plateau. To aid in identification of infants at risk for significant hyperbilirubinemia, healthcare providers can assess breastfeeding adequacy and perform bilirubin screening at the 24th−48th HOL. Registration No. (RGAO-2016-0686).